POST-CORONAVIRUS DISEASE 2019 DE QUERVAIN’S THYROIDITIS – A CASE REPORT AND LITERATURE REVIEW - SAFWAN, MOHAMAD; KN, VIJAYAN; NAJEEB; TG, JITHU (Innovare Journal of Medical Sciences, 2021)
De Quervain’s thyroiditis, also known as subacute thyroiditis (SAT), is a self-limiting inflammatory thyroid disease typically occurring a few weeks after a respiratory viral infection. A 29-year-old female with no comorbidities presented with persistent fever, neck pain, and swelling of 10 days duration. She also had tremors, fatigue, and palpitation. A careful enquiry revealed that she had been diagnosed with coronavirus disease 2019 (COVID-19) infection 6 weeks ago and had recovered uneventfully with conservative management. Her laboratories showed leukocytosis, elevated erythrocyte sedimentation rate, and C-reactive protein. Thyroid function tests (TFTs) yielded low thyroid-stimulating hormone, and high T3 and free T4. Ultrasonography neck was suggestive of thyroiditis. Thyroid scintigraphy demonstrated very low technetium uptake which confirmed SAT. Her symptoms ameliorated with nonsteroidal anti-inflammatory drug and beta-blockers and her TFTs improved during follow-up. We report this as emerging sequelae of COVID-19 infection. A persistent fever and neck pain following recent COVID-19 infection should alert clinician toward the possibility of de Quervain’s thyroiditis following severe acute respiratory syndrome coronavirus 2.